2018
DOI: 10.1016/j.enpol.2018.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Universal access to clean cookstoves: Evaluation of a public program in Peru

Abstract: The use of biofuels for heating and cooking is the main cause of indoor air pollution in developing countries, and one of the main causes of acute respiratory infections. To tackle this problem, in 2012, the Peruvian Government created the FISE Program, which subsidizes the replacement of traditional stoves with gas cookstoves. This paper describes the challenges faced during the implementation of the FISE, such as the selection of beneficiaries and the creation of a national network of suppliers for the deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…Very few studies tackled this question, and the few that did provided no actual data to back up the claims that the saved time is used for education, leisure, income generation activities and a range of other portended uses. The exceptions are Calzada and Sanz [51] who report leisure, household chores and income generation as the activities the time savings are directed towards. Filling this evidence gap is important in ensuring that realistic assumptions are made on the value of clean cooking interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Very few studies tackled this question, and the few that did provided no actual data to back up the claims that the saved time is used for education, leisure, income generation activities and a range of other portended uses. The exceptions are Calzada and Sanz [51] who report leisure, household chores and income generation as the activities the time savings are directed towards. Filling this evidence gap is important in ensuring that realistic assumptions are made on the value of clean cooking interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Gould et al (2018) found from the results of their questionnaire of 5000 households in Carchi, Ecuador that LPG stoves allowed for better time management of cooking tasks including time savings from fuelwood collection; however, delivery times of LPG are reported as being long and unreliable, which participants from the survey described as a significant time burden [50]. Calzada and Sanz (2018) found in a survey of 221,390 participants from Hua manga, Peru that switching from biomass to an LPG stove saved time spent cooking and collecting fuelwood [51]. Ortiz (2012) suggests that innovations that improve the energy supply used for cooking may free up time, improve health conditions and/or reduce the cost associated with the provision of energy for cooking, or even contribute to improved sanitation from evidence collected across Peru and Laos [52].…”
Section: Time-saving As a Driver/enabler Of Mecs Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, we conducted exploratory work during which we identified numerous studies that evaluate EE interventions. Programmes that have been studied include weatherisation programmes (Fowlie et al 2018), building code policies (Kotchen 2017), smart meters and feedback information (Shimada et al 2015), EE lightbulb market interventions (Allcott and Taubinsky 2015), energy audits in the industrial sector (Duflo et al 2013), and the uptake of efficient cookstoves in developing countries (Bensch et al 2015;Calzada and Sanz 2018). These early findings suggested a vast amount of high-quality evidence 2 in this field, and an emerging need to synthesise and draw lessons from it.…”
Section: Existing Ies and Evidence Synthesesmentioning
confidence: 99%
“…Peru has a population of about 32 million (Central Intelligence Agency, 2019), among whom approximately 6.4 million lack modern-day energy sources for domestic purposes. Ninety-three percent (93%) of Peruvians living in rural areas rely on BMF for heating water, cooking, and household lighting (Calzada & Sanz, 2018;Central Intelligence Agency, 2019;INEI, 2007).…”
Section: Introductionmentioning
confidence: 99%